Design and Validation of an Instrument for Selecting Spontaneous Volunteers During Emergencies in Natural Disasters - Marin-Caihuan, J; Bonacic-Castro, C; Martinez-Diaz, P; Contreras-Ramirez, D (Elsevier Ltd, 2021)
An instrument for selecting spontaneous volunteers can facilitate efficient decision making and management in large scale natural disasters. This study aimed to design and validate an instrument for selecting spontaneous volunteers during natural disasters in Chile. A mixed-methods study was realized. In the qualitative component, the instrument s items were derived from a competence profile for spontaneous volunteers, which was defined through interviews with disaster risk management experts. In the quantitative component, content validity was assessed measuring inter-rater (expert) agreement, and construct validity was determined by confirmatory factor analysis (CFA) in a sample of 117 volunteers in Chile, who answered the instrument. The instrument s preliminary version comprised 45 items and 5 dimensions of competence (knowledge, skills, behavior, motivation, and social desirability). The expert raters had a good degree of agreement (ICC = 0.581, p < 0.001), suggested the elimination of 10 items and the modification of 9 items. Finally, the CFA confirmed the 5-dimension structure for a total of 18 items. Fit was found to be adequate (χ2(125) = 145.38, p = 0.1027; RMSEA = 0.039; CFI = 0.938; and TLI = 0.924) and internal consistency was deemed acceptable (α = 0.74). The reliability and validity of the proposed instrument for selecting spontaneous volunteers suggests that it can be used to support the efforts of local humanitarian relief organizations. © 2021 Elsevier Ltd